Analisis Konsumsi Dan Produksi Minyak Kelapa Sawit Di Indonesia Dengan Menerapkan Metode Moving Average - Intan Giri Anjani; Alshalva Berliana Saputri; Azka Nabalah Putri Armeira; Dwi Januarita (JURIKOM (Jurnal Riset Komputer), 2022)
Palm oil has become a leading commodity for economic improvement in Indonesia. Currently, many people depend on the oil palm plantation sector. In the palm oil supply chain, there are business actors from upstream to downstream. But currently, palm oil export activities in the world are increasing. Thus causing palm oil in Indonesia to be scarce and expensive. This study discusses the analysis of consumption and production of palm oil in Indonesia by using the moving average method to forecast the amount of consumption and production of palm oil in 2022. Then analyzed using descriptive analysis method. The data source in this study is based on data available from BPS (Central Bureau of Statistics). From the forecasting results, the results show that palm oil consumption in Indonesia in 2022 has increased by 10.36% or 1.643 million tons from the amount of palm oil consumption in 2021 which is only 15.857 million tons. This is a good thing because the annual consumption of palm oil continues to increase significantly